(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Of the vitamins of Group B, B1, B6 and B12 have neuroprotective effects. Vitamin B12 is essential for lipid metabolism, hematopoiesis, and has neuroprotective effects. At the molecular level, many synergistic interactions of vitamins B1, B6 and B12 have a significant impact force on the metabolism of amino acids, carbohydrates and lipids, the formation of neural structures, the hematopoiesis system. The importance of the synergy of vitamins B1, B6 and B12 at the molecular level are important vitamins for the Prevention of neuroprotection and cerebrovascular pathology.